LEADERSHIP IN SMALL ISOLATED GROUPS - NELSON, PAUL D. (1962)
Behavioral characteristics studies associated with leader esteem were conducted with a sample of ten designated leaders from small Antarctic stations. Supporting the results obtained in other studies of leadership in small, primary, living-working groups under confining and isolated conditions, esteemed leaders ip was found to be a correla e of a relatively democratic leadership orientation, a leadership style characterized by leader participation with the men, by a personal man-to-man relationship between leader and men, and by a leader who respects and seeks the opinions of his men in matters which directly concern them. The preceding style of leadership is most effective in the small station setting for the fooling reasons: First, it facilitates a psychological distance between leader and men which is compatable with the physical and status distances prescribed by the group situation. Secondly, it seems likely to result in decisions which are supported personally by the men and decisions which are based upon the best information possible under the circumstances.